Evaluation of Anterior Vertebral Interbody Fusion Using Osteogenic Mesenchymal Stem Cells Transplanted in Collagen Sponge. Issue 4 (May 2016) - Yang, Wencheng; Dong, Youhai; Hong, Yang; Guang, Qian; Chen, Xujun
Abstract : Study Design: The study used a rabbit model to achieve anterior vertebral interbody fusion using osteogenic mesenchymal stem cells (OMSCs) transplanted in collagen sponge. Objective: We investigated the effectiveness of graft material for anterior vertebral interbody fusion using a rabbit model by examining the OMSCs transplanted in collagen sponge. Summary of Background Data: Anterior vertebral interbody fusion is commonly performed. Although autogenous bone graft remains the gold-standard fusion material, it requires a separate surgical procedure and is associated with significant short-term and long-term morbidity. Recently, mesenchymal stem cells from bone marrow have been studied in various fields, including posterolateral spinal fusion. Thus, we hypothesized that cultured OMSCs transplanted in porous collagen sponge could be used successfully even in anterior vertebral interbody fusion. Methods: Forty mature male White Zealand rabbits (weight, 3.5–4.5 kg) were randomly allocated to receive one of the following graft materials: porous collagen sponge plus cultured OMSCs (group I); porous collagen sponge alone (group II); autogenous bone graft (group III); and nothing (group IV). All animals underwent anterior vertebral interbody fusion at the L4/L5 level. The lumbar spine was harvested en bloc, and the new bone formation and spinal fusion was evaluated using radiographic analysis, microcomputed tomography, manual palpation test, and histologic examination at 8 and 12 weeks after surgery. Results: New bone formation and bony fusion was evident as early as 8 weeks in groups I and III. And there was no statistically significant difference between 8 and 12 weeks. At both time points, by microcomputed tomography and histologic analysis, new bone formation was observed in both groups I and III, fibrous tissue was observed and there was no new bone in both groups II and IV; by manual palpation test, bony fusion was observed in 40% (4/10) of rabbits in group I, 70% (7/10) of rabbits in group III, and 0% (0/10) of rabbits in both groups II and IV. Conclusions: These findings suggest that mesenchymal stem cells that have been cultured with osteogenic differentiation medium and loaded with collagen sponge could induce bone formation and anterior vertebral interbody fusion. And the rabbit model we developed will be useful in evaluating the effects of graft materials for anterior vertebral interbody fusion. Further study is needed to determine the most appropriate carrier for OMSCs and the feasibility in the clinical setting.